Cluster of neurological manifestations of rotavirus infection in children. (20th March 2012) - Day, Thomas George; Jackson, Charlotte; Bryant, Penelope Ann
Abstract : Rotavirus infection in children in the resource-rich countries is usually benign but complications are reported rarely. Four children presented within 4 weeks with neurological symptoms and stool virology positive for rotavirus. All four made a quick recovery and were discharged home after a few days without medication. At 6 weeks all were well, with no further neurological episodes. This is the first reported cluster of this nature. Potential mechanisms for how rotavirus causes its rare neurological complications are briefly discussed, along with clinical implications for clinicians managing such patients.